Proteome-Wide and Protein-Specific Multi-Epitope Vaccine Constructs Against the Rift Valley Fever Virus Outbreak Using Integrated Omics Approaches - Albutti, Aqel (Frontiers in Microbiology, 2022)
Rift Valley fever (RVF) is a viral disease caused by a member of the Bunyavirales family causing severe infections reported in humans. The negative sense single-stranded RNA en-veloped virus called RVF virus is able to infect both animals and humans. The symptoms associated with these infections spans from minor (fever and headaches) to severe (menin-goencephalitis and hemorrhagic fever syndrome) symptoms. Despite the outbreaks of RVF virus reported in different parts of the world, still no effective therapy is available. Herein, the development of efficient vaccine is critical for the control of RVF virus associated infections. Moreover, computational vaccine approaches are helpful in the design of specific, safe and stable peptides-based designs as compared to conventional methods of vaccine development. In this study, the RVF virus whole proteome comprising of four proteins (NP, L, GP and NSP) was screened to find each protein specific putative vaccine epitope sequences (T cell, B cell and HTL). These shortlisted epitopes were then combined with flexible linkers to design protein specific and proteome wide immunogenic multi epitopes-based vaccine constructs. The results revealed that these multi-epitopes vaccine constructs (MEVCs) are strongly anti-genic and non-allergenic in nature. The efficacy of these constructs was further validated by docking with immune receptors which revealed strong binding interactions with human TLR8. Using MD simulation approach the binding stability and residual flexibility of the best vaccine construct (proteome-wide) was confirmed which revealed stable dynamic and favourable features. Furthermore, in-silico cloning and immune simulation analysis confirmed the ex-pression and production of immune factors i.e., IgM, IgG, IL-6 against the proposed vaccine designs. Additionally, all the constructed MEVCs have been 3D modelled and evaluated for potential immunization against RVF virus. Finally, the proteome wide vaccine candidate (MEVC-PW-RVFV) with the highest immune reinforcement potential provides new insights into the development of future vaccine development against the emerging RVF virus.